2015
DOI: 10.11648/j.ijnfs.20150401.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Composite Blends of Fermented Fenugreek and Wheat Flour to Assess Its Suitability for Bread and Biscuit

Abstract: Flour of fenugreek supplemented at 5, 10, and 15% levels with wheat flour was assessed for the production of bread and biscuit to improve nutritional profile. Germinated fenugreek flour samples had 29.89% crude protein, 7.91% crude fat, 11.35% crude fiber and 2.94% ash on dry weight basis. The wet gluten, falling number, and water activity of wheat flour reduced on incorporation of germinated fenugreek flour while the foaming capacity, water and oil absorption increased for bread and biscuit blended wheat flou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Germinated fenugreek seed powder has been applied to bread, and biscuits to improve flour quality, nutritional quality, mineral content, acceptability, to reduce gluten content [ 915 ]. Water extract of fenugreek seed has been applied to Injera to enhance crude fiber, crude protein, minerals, crude fat content, and to lower the microbial growth [ 327 ].…”
Section: Food Industry Application Of Selected Spicesmentioning
confidence: 99%
“…Germinated fenugreek seed powder has been applied to bread, and biscuits to improve flour quality, nutritional quality, mineral content, acceptability, to reduce gluten content [ 915 ]. Water extract of fenugreek seed has been applied to Injera to enhance crude fiber, crude protein, minerals, crude fat content, and to lower the microbial growth [ 327 ].…”
Section: Food Industry Application Of Selected Spicesmentioning
confidence: 99%
“…Pumpkin belongs to the Cucurbitaceae family generally characterized by climbing herbaceous vine with tendrils , grown widely all over the world and pumpkin is a rich source of nutrients that may help improve products Kasaye and Jha (2015). It has been used traditionally in many countries as medicine such as India, Mexico, Brazil, America and Argentina Jia et al,(2003).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal level of incorporation of FSH flour, based on sensory quality in muffins was found to be 10%. Kasaye et al (2015),showed that the flour of fenugreek supplemented at 5, 10 and 15% levels with wheat flour was assessed to produce bread. The sensory evaluation of products has exhibited that 5 and 10% for bread and 5% for biscuit, fermented fenugreek flour supplemented with wheat flour resulted highly acceptable bread and biscuit compared with control samples.…”
Section: Introductionmentioning
confidence: 99%